First record of the genus Abrhexosa Freeman from Mexico, with the description a new species, and two new species and new records of the genus Swammerdamella Enderlein (Diptera: Scatopsidae) - Huerta, Heron; Dzul, Felipe (Zootaxa, 2013)
The genus Abrhexosa Freeman is reported for the first time from Mexico, with the description of a new species, A. patriciae sp. nov., very close to A. panamensis (Cook, 1956). Two new species of the genus Swammerdamella Enderlein, 1912 from Mexico are described and illustrated: Swammerdamella amorimi sp. nov. and S. amacuzacae sp. nov. Swammerdamella mojingae Cook, 1956 is reported for the first time for Mexico, and new records are included for S. marginata Cook, 1956. A key for the species of Swammerdamella of Mexico is provided.